2018
DOI: 10.7196/samj.2018.v109i1.13268
|View full text |Cite
|
Sign up to set email alerts
|

Cost of intensive care services at a central hospital in South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“… 35 In another study, Mahomed & Mahomed estimated daily ICU costs in South Africa for other conditions. 36 Although their estimates were higher than ours, Mahomed & Mahomed found that human resource costs was the highest cost driver of total ICUs costs, similar to our findings. 36 There are a few limitations of our study worth highlighting.…”
Section: Discussionsupporting
confidence: 89%
“… 35 In another study, Mahomed & Mahomed estimated daily ICU costs in South Africa for other conditions. 36 Although their estimates were higher than ours, Mahomed & Mahomed found that human resource costs was the highest cost driver of total ICUs costs, similar to our findings. 36 There are a few limitations of our study worth highlighting.…”
Section: Discussionsupporting
confidence: 89%
“…Intensive care services are very expensive and are one of the largest drivers of hospital costs, even in public hospitals where the cost per patient per ICU day has been estimated at R22,700 [2]. Discovery Health, the largest private medical scheme in the country, at the time reported that the average cost of all COVID-19 hospital admissions across its members was R84,708.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive care services are very expensive and are one of the largest drivers of hospital costs, even in public hospitals where the cost per patient per ICU day has been estimated at R22,700. [2] Discovery Health, the largest medical scheme in the country, at the time reported that the average cost of all COVID-19 hospital admissions across its members was R84,708. The average cost of an ICU admission for its members was substantially higher - at R169,525 and these admissions were also reported to have the “highest variation in cost”.…”
Section: Background and Aim Of Studymentioning
confidence: 99%